Do immigrants improve the health of native workers? - Osea Giuntella (IZA World of Labor, 2014)
Public debate on immigration focuses on its effects on wages and employment, yet the discussion typically fails to consider the effects of immigration on working conditions that affect workers' health. There is growing evidence that immigrants are more likely than natives to work in risky jobs, as they are more inclined to take on physically intensive tasks. Recent studies show that as immigration rises, native workers are pushed into less demanding jobs. Such market adjustments have positive impacts on the health of the native workers.
Keywords: I12; J24; J61; 330; immigration; occupational choice; job quality; health